2021
DOI: 10.1182/bloodadvances.2020003707
|View full text |Cite
|
Sign up to set email alerts
|

HLA-haploidentical TCRαβ+/CD19+-depleted stem cell transplantation in children and young adults with Fanconi anemia

Abstract: We report on the outcome of 24 patients with Fanconi anemia (FA) lacking an HLA matched related or unrelated donor, given an HLA-haploidentical T-cell receptor αβ (TCRαβ+) and CD19+ cell-depleted hematopoietic stem cell transplantation (HSCT) in the context of a prospective, single-center phase 2 trial. Sustained primary engraftment was achieved in 22 (91.6%) of 24 patients, with median time to neutrophil recovery of 12 days (range, 9-15 days) and platelet recovery of 10 days (range, 7-14 days). Cumulative inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…In line with this observation, we recently reported a low incidence of GVHD, resulting in excellent outcomes in 24 FA patients treated with this type of haplo-HSCT platform. 34 Moreover, the GRFS probability, which is used as a surrogate for quality of life, is remarkably high in our cohort.…”
Section: Discussionmentioning
confidence: 74%
“…In line with this observation, we recently reported a low incidence of GVHD, resulting in excellent outcomes in 24 FA patients treated with this type of haplo-HSCT platform. 34 Moreover, the GRFS probability, which is used as a surrogate for quality of life, is remarkably high in our cohort.…”
Section: Discussionmentioning
confidence: 74%
“…The mean (SD) cumulative incidence of 30-day neutrophil engraftment was 96.4% (0.08%), with a median (range) time of 12 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) days. The median (range) time to attaining a platelet count of ≥20 × 10 9 /L was 13 (6-180) days.…”
Section: Engraftment Gf and Chimerismmentioning
confidence: 99%
“…Recent decades have witnessed improved survival in HCT for FA, including haplo-HCT. [5][6][7][8][9][10][11] The long-term side-effects of HCT, especially the increased risk of secondary malignancies, have become critical considerations. In patients with FA, intrinsic DNA repair defects lead to unique hypersensitivity to irradiation and alkylating agents.…”
Section: Introductionmentioning
confidence: 99%
“…As another potential stem cell source for patients with FA, the EBMT-Severe Aplastic Anemia Working Party (SAAWP) reported promising outcomes in patients who underwent haploidentical HCT with in vivo T-cell depletion, with a 2-year event-free survival (EFS) of 86% [19]. A study from Italy reported that haploidentical HCT with ex vivo depletion of T-cell receptor α/β + and CD19 + cells was successfully performed in patients with FA, with a 5-year EFS of 86% [20]. These results suggest unrelated CBT and haploidentical HCT as promising strategies; however, these procedures should be performed in experienced centers [14][15][16]21].…”
Section: Current Status and Future Perspectives Of Allogeneic Hematop...mentioning
confidence: 99%